1999
DOI: 10.1055/s-1999-13961
|View full text |Cite
|
Sign up to set email alerts
|

Acetogenins and Other Compounds from Rollinia emarginata and Their Antiprotozoal Activities

Abstract: Bioactivity-directed fractionation of the MeOH extract of the stem barks of Rollinia emarginata resulted in the isolation of six compounds, four acetogenins, rolliniastatin-1, sylvaticin, squamocin, and rollidecin B, one lignan, lirioresinol B, and an oxoaporphine, liriodenin. Their structures were determined by spectroscopic analysis and their in vitro leishmanicidal and trypanocidal properties are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…However, some Rollinia species are used in traditional medicine for tumour treatment (Zeng et al, 1996). Prior studies have shown that crude extracts from Rollinia species display in vitro activities against Leishmania braziliensis, Leishmania amazonensis and Leishmania donovani promastigotes and Trypanosoma cruzi trypomastigotes (Février et al, 1999). Antimicrobial and antifungal activities have also been described (Caetano and Dadoun, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…However, some Rollinia species are used in traditional medicine for tumour treatment (Zeng et al, 1996). Prior studies have shown that crude extracts from Rollinia species display in vitro activities against Leishmania braziliensis, Leishmania amazonensis and Leishmania donovani promastigotes and Trypanosoma cruzi trypomastigotes (Février et al, 1999). Antimicrobial and antifungal activities have also been described (Caetano and Dadoun, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Against different Leishmania and T. cruzi strains at 250 µg/mL inhibitory activity up to 89% and 67% was reported for rolliniastatin-1 (3) and squamocin (4) [35]. The leishmanicical activity was related to the number of hydroxy groups on these acetogenins.…”
Section: Organic Acids Lipids and Acetogeninsmentioning
confidence: 99%
“…The secoiridoid amarogentin (35) isolated from the upper parts of Swertia chirata (Loganiaceae) is a promising compound with leishmanicidal activity. This compound inhibited DNA-Topoisomerase I activity from Leishmania donovani at 30 µM [79].…”
Section: Iridoidsmentioning
confidence: 99%
“…The oxoaporphine alkaloid liriodenine (142) and the zwitterionic derivative N-methylliriodendronine (143) isolated from the African medicinal shrub Stephania dinklagei (Menispermaceae) exhibited activity against L. donovani promastigotes (IC 50 values of 15 and 19 µM , respectively). However, these alkaloids were less active against L. donovani amastigotes, and 142 displayed an IC 50 of 27 µg/mL against KB cells [114].…”
Section: Other Alkaloidsmentioning
confidence: 99%